Methodological Approaches of Scenario Modeling and Forecasting of Development of Agricultural Sector of the Russian Economy under Conditions of Foreign Policy and Conjunctural Changes (with the Republic of Tatarstan as an example) - Safiullin, Marat Rashitovich; Elshin, Leonid Alekseevich; Prygunova, Mariya Igorevna (International Journal of Economics and Financial Issues, 2015)
The subject of the research includes peculiarities and regularities of the reaction of the agricultural sector of the Russian economy on the changing conditions of the economic management formed by the pressure of sanctions on the national economy. The object of the research includes the agricultural sector of the Russian economy (with the Republic of Tatarstan as an example). The authors particularly consider such aspects as the dependence between the dynamics of the production level of agricultural products of the Republic of Tatarstan on the dynamics of the index related to the economic activity of the region. On this basis the forecasting model of the development of agriculture in the Republic of Tatarstan is developed taking into account various scenarios of sanctions pressure on the national economy of the Russian Federation. Special attention is paid to the issues related to the analysis of the development of the agricultural sector of the republic economy in the short-term perspective in order to define its perspective competitiveness and stability of development. Keywords: regional agricultural sector, expectations of economic agents, economic activity, sanctions pressure, scenario modeling of the agriculture development. JEL Classifications: F42; F47; Q13; Q14; Q17; Q18